Estrategias de marketing para el incremento de ventas de la cafetería crêpes de Francia en la ciudad de Guayaquil - Huilca Chiriguaya, María José (2017)
The development of the present study was directed to the diagnosis of the problematic of Crêpes de Francia coffee shop, a business dedicated to the elaboration and commercialization of crêpes, frappes, coffee varieties and waffles; located its establishment in Mall del sol, where; The lack of knowledge about the products offered by the cafeteria, the lack of publicity actions and lack of knowledge about the correct marketing tools have led to its low positioning and poor brand image, together with the decisive factors of purchase not controlled from the beginning Of commercial operation have prevented attracting more customers, have created a gap to business growth; Which is why we examine the marketing strategies to be used to build the type of positioning, achieve the increase in sales that the owner aspires by applying previously defined marketing strategies, such as positioning strategies, market penetration, dissemination and Promotion of the products that are offered and the use of sensorial marketing so that the improvement of the establishment generates an impact on the market share of the business. For the determination of strategies, a previous market study was carried out in which the consumer's behavior was known, his opinions, suggestions and his degree of satisfaction; In the same way, potential customers were analyzed by searching their preferences and in the top of mind to know the most influential brands; Through the survey, this being a field research of quantitative approach that allowed us to formulate marketing objectives and to plan the necessary corrective measures to be performed in order to comply with them……